2016
DOI: 10.5114/fn.2016.64816
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed integrin expression in the vascular media in CADASIL

Abstract: A b s t r a c t CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) is an inher-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…Such rounded appearance is characteristic of detached cells which are devoid of physical influences from ECM. Moreover, our previous study revealed disturbed expression of integrin subunit β-1 in CADASIL vessels that my lead to myocytes detachment from ECM [3]. This finding as well as the results reported by other authors suggests that degeneration and loss of VSMC can be secondary to pro-life or protecting signals originating from ECM.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Such rounded appearance is characteristic of detached cells which are devoid of physical influences from ECM. Moreover, our previous study revealed disturbed expression of integrin subunit β-1 in CADASIL vessels that my lead to myocytes detachment from ECM [3]. This finding as well as the results reported by other authors suggests that degeneration and loss of VSMC can be secondary to pro-life or protecting signals originating from ECM.…”
Section: Introductionsupporting
confidence: 70%
“…The diagnosis of CADASIL was established on the basis of ultra-structural criteria, i.e., the presence of pathognomonic for the disease GOM deposits in vessel walls [4], and in the majority of cases was additionally confirmed by genetic studies. Clinical details of the examined CADASIL material are presented in our previous paper [3].…”
Section: Methodsmentioning
confidence: 99%
“…Affected myocytes acquire variable nuclear sizes and shapes with abnormal chromatin appearance [ 12 ] that is related to the stress caused in the endoplasmic reticulum (ER) by accumulation of mutant NOTCH3 extracellular domain [ 36 , 56 ]. Consistent with the degeneration of VSMCs, decreased expression of integrin beta1 subunit and beta1 immunoreactivity were reported in small arteries, arterioles and capillaries in CADASIL [ 11 ].…”
Section: Introductionsupporting
confidence: 66%
“…They have lost their normal circumferential orientation in arterial walls and are not closely packed but separated from each other. Such isolated myocytes are round‐shaped which suggests their loss of adhesion to extracellular matrix . Ultrastructural studies of VSMCs showed their vacuolization, enlarged mitochondria, and a presence of deposits of granular osmiophilic material (GOM) within indentations of the cell membrane or in the tunica media.…”
Section: Introductionmentioning
confidence: 99%